Using Primo for undergraduate research: a usability study. Issue 4 (21st November 2016) - Kliewer, Greta; Monroe-Gulick, Amalia; Gamble, Stephanie; Radio, Erik
Abstract : Purpose: The purpose of this paper is to observe how undergraduate students approach open-ended searching for a research assignment, specifically as it affected their use of the discovery interface Primo. Design/methodology/approach: In total, 30 undergraduate students were provided with a sample research assignment and instructed to find resources for it using web tools of their choice, followed by the Primo discovery tool. Students were observed for 30 minutes. A survey was provided at the end to solicit additional feedback. Sources students found were evaluated for relevance and utility. Findings: Students expressed a high level of satisfaction with Primo despite some difficulty navigating through more complicated tasks. Despite their interest in the tool and previous exposure to it, it was usually not the first discovery tool students used when given the research assignment. Students approached the open-ended search environment much like they would with a commercial search engine. Originality/value: This paper focused on an open-ended search environment as opposed to a known-item scenario in order to assess students' preferences for web search tools and how a library discovery layer such as Primo was a part of that situation. Evaluation of the resources students found relevant were also analyzed to determine to what degree the students understood the level of quality they exhibited and from which tool they were obtained.